Caracterização dos dados brasileiros de haplótipos Y-STR no Y-Chromosome haplotype reference database e análise da ancestralidade da linhagem masculina brasileira - Baitello, Maria Eduarda Lopes (2018)
In human identification, the Y-chromosome has several applications that aid in forensic routine, but a haplotype database of Y chromosome Short Tandem Repeat (Y-STR) is needed to estimate the frequency of a genetic profile. The integration of haplotypic data from different Brazilian regions is only valid if there is no population substructure. Objectives: To characterize the Brazilian population structure based on data from Y-STR haplotypes deposited in the Y Chromosome Haplotype Reference Database (YHRD), as well as to analyze the ancestry of the male lineage of the country. Material and Methods: Data from Brazilian populations submitted to the YHRD database, update 56, were retrieved from the literature. The genetic distance (FST and RST), population structure (AMOVA) and haplotype diversity (Nei formula) analyzes were performed using populations genotyped for the Yfiler® kit and available in the literature. For analysis of Brazilian ancestry, haplogroups based on Y-STR haplotypes were inferred. Results: Analyzes were carried out involving 6,553 Y-STR haplotypes of Brazilian populations of Native American, Admixed and European origin. Among the Brazilian Native American populations, high genetic distance values were found. In the Admixed and European populations, all pairs presented low values of genetic distance, with emphasis on the North region and the populations of Belém (PA) and Boa Vista (RR), which, despite low genetic distance, showed significant P-value (P <0.00022). The haplotypic variation within Admixed populations separated by region was 99.55% (P <0.00000) and only 0.38% (P <0.00000) and 0.07% (P<0.10119) between populations within regions and between regions of Brazil, respectively. The haplotypic diversity of the Admixed populations was 0.99993 and the discrimination capacity was 87.6%. In European populations the values were 0.99983 and 96.8%, respectively, while in Native American populations, 0.98377 and 45.25%, respectively. Analysis involving 4,718 haplogroups of 22 Brazilian populations of Admixed origin and two populations of European origin revealed essentially European ancestry in Brazil, with emphasis on the south and center-west regions. The regions with the greatest African contribution were the northeast and southeast. Among 16 populations of Native American origin, 342 haplogroups were inferred, which revealed Amerindian ancestry represented in 94.15% of the samples. Conclusion: Taking into account the Yfiler® system, Brazilian Admixed and European metapopulations do not show population substructure, pointing out that a national base of Y-STR haplotypes can be used to estimate the haplotype frequencies of these populations in forensic cases. In addition, our findings indicate an essentially European ancestry of the Brazilian male lineage, establishing the history of colonization and settlement in Brazil.